STEM Education in Indonesia: Science Teachersâ€™ and Studentsâ€™ Perspectives - Anna Permanasari; Bibin Rubini; Oktian Fajar Nugroho (Yayasan Keluarga Guru Mandiri, 2021)
STEM education in indonesia has become a commitment for all of stakeholders in the field of science education in the last several years. All education participants agree to increase the popularity of STEM education in various parties, especially teachers and students. The research has been conducted to see to what extent science teachers in the secondary school interpret and understand STEM education and how Students pertain toward STEM learning. The research was conducted with a descriptive method using a survey approach. A set of questionnaire which comprises open-ended and closed-ended questions about teachersâ€™ and studentsâ€™ perceptions and understanding regarding STEM education were developed and applied. Responses from science teachers as well as students were then analysed through interpretative methods in which the participantsâ€™ own meanings and points of view were sought. The result indicated that STEM education is quite well understood by science teachers. Most of teachers show the same level of understanding toward STEM Education. Unfortunately, not many teachers have applied the STEM approach for science learning in the classroom. This is led to the weak understanding of STEM learning in studentsâ€™side. Most of students did not familiar with â€œSTEM learningâ€ term. Based on the research, it is reccomended that the science teachersâ€™ training and development should be reorientated and implemented through lesson analysis with various best practices on STEM learning systematically and continually.